Odpowiedź :
a) 6+y=8
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4
a) 6+y=8
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4
a) 6+y=8
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4
y=2
b) x+1=6
x=5
c) 12-2y=6
-2y=-6
y=3
d) -x+6x=5
5x=5
x=1
y=-2
e) 3x+2x=10
5x=10
x=2
y=4